Constructive Alignment Approach for Capstone Project with Industry Involvement: Case Study in Malaysia University - Hermawan Nugroho (ASEAN Journal of Science and Engineering Education, 2022)
A capstone project is a project-based learning course designed to bring aspects of an undergraduate student’s experience.  To have an effective capstone project, it is imperative to properly design the curriculum with involvement from the industry.  To improve the performance of the capstone project course, we used the constructive alignment approach to design the curriculum.  In constructive alignment, we mapped the intended learning outcomes, the assessment tasks and the teaching/learning activities interchangeably with each other.  Experiments were conducted with students enrolled in the capstone project courses in our university from February 2016 to May 2017. The result shows that the new design was able to improve the attainment scores for both learning outcomes and program outcomes. This improvement was also in line with marks by industry experts indicating good potential.